Kaalamang Pagsasaka sa Himpapawid - School-on-the-Air project on Climate Smart Agriculture (SOA–CSA) in Cagayan Valley: Manual of Operations - Department of Agriculture, Philippines; Philippine Federation of Rural Broadcasters; Philippine Agriculture Journalists, Inc.; Philippine Rice Research Institute; Cagayan Valley Agriculture and Resources Research and Development Consortium; CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This manual serves as a guide for all partners involved in the School-on-the-Air project on Climate Smart Agriculture (SOA–CSA) in Cagayan Valley, Philippines in February 2018. It has five chapters: (1) introduction, (2) implementation scheme, (3) organizing and conducting the SOA, (4) logistical requirements, and (5) reporting procedures. It is an updated adaptation of an earlier SOA handbook produced by the DA-Agricultural Training Institute (DA–ATI) with the PFRB for the Agrikulturang Makamasa program in 1998.